Implementasi Model Pembelajaran Contextual Teaching And Learning (CTL) Dalam Pelajaran IPA Di Sekolah Dasar - Kurniasih, Deni (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
In learning science, the problem that arises is how to make learning and presenting science concepts fun for students. For success in learning, learning must be fun, namely the material presented to students already exists in their daily lives. Contextual Teaching and Learning (CTL) is a learning approach that links the material being taught with students' real world situations and encourages students make connections between the knowledge learned and its implementation in their daily lives. The application of the Contextual Teaching and Learning (CTL) learning model in science learning is to apply a learning that includes all the components contained in Contextual Teaching and Learning (CTL). In the implementation of learning, the teacher maximizes the learning process so that learning objectives can be achieved in accordance with the Competency Standards and student conditions. Through learning using the Contextual Teaching and Learning (CTL) approach, it is hoped that students can find solutions to problems from the knowledge they have, and it makes students play an active role when the teaching and learning process takes place.